Strategic Planning Using SWOT Matrix and QSPM: Case Study Analysis at Prima Fotocopy Center - Devina Putri; Tri Siwi Agustina; R. Aj. Diajeng Widiani H.; Nikita Claudia (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Prima Fotocopy Center is a photocopying center business that provides black and white and color photocopying services. Prima Photocopy Center was established on January 20, 1998, in Bima City, West Nusa Tenggara. The study was conducted for 3 weeks, namely on December 18–January 7, 2024 in Bima City, West Nusa Tenggara. The purpose of this study is to determine the strategic planning for the development of "Prima Fotocopy Center" using the SWOT and QSPM matrices in achieving competitive advantage. This study uses a qualitative method that collects data through interviews with owners, employees, and customers. Data is collected to identify internal and external factors. In this study, data processing is carried out using the IFE (Internal Factor Evaluation), EFE (External Factor Evaluation), IE (Internal External), SWOT (Strengths, Weaknesses, Opportunities, Threats), SPACE Matrix, and QSPM (Quantitative Strategic Planning Matrix) matrices, where this method is used to identify and evaluate strengths and weaknesses as well as opportunities and threats in the market environment. This study also uses source triangulation and technical triangulation techniques in a single case study analysis. The results show that Prima Fotocopy Center leverages its strengths such as digital service quality and market competition. In the IE Matrix, Prima Fotocopy Center is in quadrant II, indicating an average position that has achieved growth and development strategies such as market penetration and product development. The QSPM Matrix determines the attractiveness of the strategy to be prioritized based on the highest score. In conclusion, Prima Fotocopy Center is obliged to improve its online services to increase customer convenience and update its digital photocopying system to meet customer needs in the digital era.